The effect of earnings management and tax aggressiveness on shareholder wealth and stock price crash risk of German companies. Issue 1 (3rd May 2019) - Neifar, Souhir; Utz, Sebastian
Abstract : Purpose: The purpose of this paper is to examine the influence of earnings management (EM) and tax aggressiveness (TA) on shareholder wealth and on stock price crash risk (SPCR) of German companies. Design/methodology/approach: The sample comprises 820 firm-year observations of 188 non-financial companies listed on German stock exchanges from 2008 to 2014. The authors apply generalized least square panel regression to overcome autocorrelation and heteroscedasticity problems. Findings: EM and TA are not related in terms of affecting shareholder wealth and SPCR. EM has no impact on shareholder wealth but significantly affects SPCR. TA has a significant positive effect on shareholder wealth but no impact on SPCR. Thus, EM practices applied within German companies are non-opportunistic, as they do not affect shareholder wealth and decrease SPCR. TA practices are also non-opportunistic, as they increase shareholder wealth and do not affect SPCR. Research limitations/implications: This study provides insights that can improve managers' accounting choices (EM vs TA) and alleviate investor concerns about the effect of managers' manipulation strategies. Considering other variables affecting TA, such as discretionary book tax differences, may add further insights into this discussion. The analysis of and comparison with other markets may shed more light on the validity and generalizability of the results. Practical implications: This study recommends that investors must take into consideration the accounting variables to ensure better investment decisions and highlight the importance of CEO choices on market reaction. Originality/value: The investigation of the mutual impact of EM and TA on shareholder wealth and SPCR is novel, and so too is the analysis of whether EM and TA are complementary or substitute for each other in this relationship.